Revisiting the Idealizing Transferences: "Needful Things" and the Faustian Bargain. Issue 3 (3rd July 2017) - Lyons-Ruth, Karlen
Abstract : A number of analytic writers have commented on the dilemma of the child "in the service of the parent." More recently, developmental research studies have deepened our understanding of the developmental onset, trajectories, and correlates associated with role confusion in the parent-child relationship. In the current article, two clinical cases are presented around which to integrate analytic and research insights into the nature of both pathological and facilitating idealizing transferences, as well as the patient's inner experience of role-confusion in the relationship with the parent. The case material illuminates how the child protects parts of himself from invasion and devastation through self-fragmentation and the subsequent organization of a false self that can adapt to the imperative to sustain a fragile attachment relationship with a disturbed parent. The developmental literature grounds this trajectory toward role confusion in the distress and disorganization of attachment strategies apparent in the first 2 years of life, which is replaced over the preschool years by the false-self organization of the caregiving child. By late adolescence, these role-confused relationships are often characterized by borderline features marked by recurrent suicidality and self-injury.